2021
DOI: 10.1080/87565641.2021.1966431
|View full text |Cite
|
Sign up to set email alerts
|

Top-down Inhibitory Motor Control Is Preserved in Adults with Developmental Coordination Disorder

Abstract: Two paradigms were employed to disentangle information processing from executive motor inhibition in adults with Developmental Coordination Disorder (DCD). Choice Reaction and Stop Signal Tasks were compared between 13 adults fulfilling DSM-5 DCD criteria and 42 typically developing adults. Additional analyses included 16 probable DCD (pDCD) participants, who had motor difficulties but did not fulfil DSM-5 criteria. Analyses employed frequentist and Bayesian modeling. While DCD+pDCD showed slower reaction time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 74 publications
(85 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, our study employed standardized, widely used tests of executive functions, in contrast to a recent study using a computerized assessment aimed at ecological validity but with relatively limited research on its psychometric properties (Mayes et al, 2023). As opposed to other studies (e.g., Kirby et al, 2010; Mayes et al, 2023; Tal Saban et al, 2014), we excluded participants with ADHD, based on comprehensive information gathered prospectively since birth (Schiavone et al, 2019) instead of a self-reported diagnosis (e.g., He et al, 2018; Mayes et al, 2021). Our results thus provide evidence that the impairment in executive functions associated with childhood MD may also be independent of concurrent ADHD in adults.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, our study employed standardized, widely used tests of executive functions, in contrast to a recent study using a computerized assessment aimed at ecological validity but with relatively limited research on its psychometric properties (Mayes et al, 2023). As opposed to other studies (e.g., Kirby et al, 2010; Mayes et al, 2023; Tal Saban et al, 2014), we excluded participants with ADHD, based on comprehensive information gathered prospectively since birth (Schiavone et al, 2019) instead of a self-reported diagnosis (e.g., He et al, 2018; Mayes et al, 2021). Our results thus provide evidence that the impairment in executive functions associated with childhood MD may also be independent of concurrent ADHD in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies of cognitive impairment in adults with a history of childhood MD or with DCD have generally relied on retrospective self-reports to establish that the participants had MD already as children (Barhoun et al, 2021;He et al, 2018;Mayes et al, 2021Mayes et al, , 2023. Retrospective self-reports of childhood symptoms may, however, not be entirely accurate in neurodevelopmental disorders (von Wirth et al, 2021).…”
Section: Cognitive Impairment Associated With Childhood Motor Difficu...mentioning
confidence: 99%
See 3 more Smart Citations